Evolutionary Explanations of the “Actuarial Senescence in the Wild” and of the “State of Senility” - Libertini, Giacinto (ScientificWorldJournal, 2006)
A large set of data suggests that progressive reduction of fitness and senile decay in vertebrates are in correlation with the decline of cell replication capacities. However, the limits in such capacities are hardly explained in evolutionarily terms by current gerontological theories that rule out fitness decline as something genetically determined and regulated, and therefore somehow favored by natural selection.Four theories are tested as possible explanations of the “increasing mortality with increasing chronological age in populations in the wild” (“IMICAW”[1]), alias “actuarial senescence in the wild”[2], and of the observed negative correlation between extrinsic mortality and the ratio between deaths due to intrinsic mortality and deaths due to extrinsic mortality. Only the theory attributing an adaptive value to IMICAW allows an evolutionary explanation for it and for the aforesaid inverse correlation, while the other three theories (“mutation accumulation”, “antagonistic pleiotropy”, and “disposable soma” th.) even predict a positive correlation.Afterwards, the same theories are tested as possible explanations for the “state of senility”[3], namely the deteriorated state of individuals in artificially protected conditions (captivity, civilization, etc.) at ages rarely or never observable in the wild. With the distinction between “damage resulting from intrinsic living processes”[4], alias “age changes”[5], and “age-associated diseases”[4,5], the same theory explaining IMICAW allows a rational interpretation of the first category of phenomena while another theory, the “mutation accumulation” hypothesis, gives an immediate interpretation for the second category.The current gerontological paradigm explaining the increasing mortality with increasing chronological age as consequence of insufficient selection should be restricted to the “age-associated diseases”. For IMICAW, it should be substituted with the concept of a physiologic phenomenon genetically determined by a balance of opposite selective pressures — strictly in terms of kin selection — and, for “age changes”, with the action of the same IMICAW-causing mechanisms at ages when selection becomes ineffective.